SOCIAL POVERTY IN TWO EXTREME CASES IN MANGGARAI-EAST NUSA TENGGARA PROVINCE - Zaka Lawang, Robert Markus (Istek Widuri Jakarta, 2021)
The aim of this article is to examine the concept of social poverty at local context of two extreme geographically rural and urban areas. The logic of the article is structured as follows. Firstly is the identification social class at urban and rural contexts, in which social poverty is taking place. Then, it is followed by describing shortly the government programs on poverty alleviation, i.e. PNPM, Dana Desa, KAT and Health Insurance, in which trust in government could be built. Theoretical analysis are mainly referring to Weber, Bourdieu, and Putnam. Social capital formation is hindered mostly by closed system of social class in urban context, and by long unresolved isolation in rural context. The implementation of the government programs could be increasing trust in government. But on the other hand, social capital at rural context had declined in its capacity to solve their own problems. The bottom-up and top-down approach in the programs coordinated by the related ministries, gave more space to the poor for participation.